The IT regulatory and standards compliance handbook - Wright, Craig; Freedman, Brian; Liu, Dale. (Burlington, MA : Syngress Pub., 2008)
This book provides comprehensive methodology, enabling the staff charged with an IT security audit to create a sound framework, allowing them to meet the challenges of compliance in a way that aligns with both business and technical needs. This "roadmap" provides a way of interpreting complex, often confusing, compliance requirements within the larger scope of an organization's overall needs. Key Features: * The ulitmate guide to making an effective security policy and controls that enable monitoring and testing against them * The most comprehensive IT compliance template available, giving detailed information on testing all your IT security, policy and governance requirements * A guide to meeting the minimum standard, whether you are planning to meet ISO 27001, PCI-DSS, HIPPA, FISCAM, COBIT or any other IT compliance requirement * Both technical staff responsible for securing and auditing information systems and auditors who desire to demonstrate their technical expertise will gain the knowledge, skills and abilities to apply basic risk analysis techniques and to conduct a technical audit of essential information systems from this book * This technically based, practical guide to information systems audit and assessment will show how the process can be used to meet myriad compliance issues.
Introduction to IT compliance -- Evolution on information systems -- The information systems audit program -- Planning -- Information gathering -- Security policy overview -- Policy issues and fundamentals -- Assessing security awareness and knowledge of policy -- An introduction to network audit -- Auditing Cisco routers and switches -- Testing the firewall -- Auditing and security with wireless technologies -- Analyzing the results -- An introduction to systems auditing -- Database auditing -- Microsoft Windows security and audits -- Auditing UNIX and Linux -- Auditing web-bases applications -- Other systems -- Risk management, security compliance, and audit controls -- Information systems legislation -- Operations security.
"How to survive an information systems audit and assessments"--Cover.
Includes bibliographical references and index.
Keywords: Information technology -- Management; Information resources management -- Auditing; Electronic books